Factors afffecting on the growth assets of sharia life insurance companies in Indonesia - Mega Mushrifah; Slamet Haryono; Bill Pangayow (Universitas Islam Negeri Walisongo Semarang, 2024)
Purpose - The objective of this research is to present a summary and examination of the impact of investment returns, claims, and premiums on asset growth in Indonesian sharia life insurance firms from 2018 to 2022.Method - This study uses quantitative methods. The study's population consists of sharia life insurance companies that are registered with the OJK, and its sample consists of seven such companies that provide complete financial reports through 2022. Panel data analysis is the data analysis technique employed in this study, and the Common Effect Model (CEM) was selected using eviws 10.Result - This study provides evidence that premiums and claims have a detrimental effect on Indonesian Islamicic life insurance businesses' asset growth. Low premiums and high claims inhibit asset growth. On the other hand, investment returns have a positive effect, because Islamicic insurance companies gain opportunities for asset growth from investments in various sectors. Therefore, claim management and optimization of investment returns are very important to encourage the growth of company assets.Implication - These findings have implications from the results of this investigation, which show that a company is better and can be considered healthy if its assets are larger.Originality - This study is the first to employ profit-sharing finance as an intervening variable.